Cargo cult in Africa: Remittances and the state in Tanzania - Peter Hansen (Danish Institute for International Studies (DIIS), 2010)
This DIIS working paper explores the current celebration of remittances in Tanzania as a magic bullet for the creation of development and economic growth. It adds to our understanding of the underlying cultural values, ideas and imaginaries expressed in remittance policies and thinking, which have until now been ignored. Within the past few years, the Tanzanian state has started to think of remittances sent by the Tanzanian diaspora as an untapped source of investment and development potential. The paper argues that the celebration of remittances by Tanzanian politicians and bureaucrats is similar to the religious sects developing across Melanesia in the 1950s and 1960s - known as cargo cults. Both remittance thinking and policy formation in Tanzania and cargo cults celebrate the transformation of the local by the miraculous arrival of wealth and goods sent by relatives living.
Keywords: 330; Rücküberweisung (Migranten); Religionsgemeinschaft; Entwicklungspolitik; Tansania